Foreign body giant cells and osteoclasts are TRAP positive, have podosome‐belts and both require OC‐STAMP for cell fusion. Issue 8 (12th June 2013) - Khan, Usman A.; Hashimi, Saeed M.; Bakr, Mahmoud M.; Forwood, Mark R.; Morrison, Nigel A.
Abstract Macrophages have the ability to fuse and form multinucleated giant cells such as Osteoclast (OCs) and FBGCs. Osteoclast stimulatory transmembrane protein (OC‐STAMP) is an important cell surface protein involved in the formation of OCs. This study sought to determine if OC‐STAMP also regulates formation of FBGCs using expression analysis and subsequent inhibition studies. qPCR and Western blot analysis showed that OC‐STAMP expression is significantly higher in FBGCs compared to control monocytes (P < 0.05). Four days following cell culture, OCs were positive for TRAP and F‐actin ring formation, but FBGCs were not. In contrast, FBGCs were positive for TRAP and showed podosome belts comprised of F‐actin on Day 8. FBGCs were subsequently plated onto dentine, but despite presenting some morphologic features of OCs (OC‐STAMP expression, TRAP reactivity, and podosome belts) they failed to resorb bone. To evaluate a role for OC‐STAMP in FBGCs, we inhibited this cell surface protein with anti‐OC‐STAMP antibody and observed that cell fusion and podosome belt formation was inhibited in both OCs and FBGCs. Our data support the hypothesis that OC‐STAMP is a regulatory molecule for FBGCs; and that they are functionally distinct from OCs, despite similarities in gene expression profile, podosome belt formation, and TRAP expression. J. Cell. Biochem. 114: 1772–1778, 2013. © 2013 Wiley Periodicals, Inc.